2018
DOI: 10.1371/journal.pone.0201053
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between personalities and social interactions affects the cohesion of the group and the speed of aggregation

Abstract: Collective decision-making plays a central role in group-living animals and can be crucial to the survival of a group and the fitness of its members. As group-level properties emerge from individual decisions, personality variation can be a major determinant of collective behaviours. Here, we explore the relationship between personality and social interactions to explain the speed and cohesion of collective decision making during the aggregation process of the American cockroach (Periplaneta americana). We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…However, to date, few studies have considered how impacts of psychoactive pollutants might be affected by social context [23,24], and fewer still have directly asked whether impacts seen in social isolation are reflective of those in a social context [25]. This is surprising given that social interactions can play an important role in mediating individual behaviour [26,27]. As a result, for group-living species, behavioural tests performed in social isolation may not accurately predict the environmental risk posed by chemical pollution.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, few studies have considered how impacts of psychoactive pollutants might be affected by social context [23,24], and fewer still have directly asked whether impacts seen in social isolation are reflective of those in a social context [25]. This is surprising given that social interactions can play an important role in mediating individual behaviour [26,27]. As a result, for group-living species, behavioural tests performed in social isolation may not accurately predict the environmental risk posed by chemical pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Often, this enhanced sociability covaries with the tendency to be more shy and cautious and also less aggressive (Budaev, 1997;Ward et al, 2004b;Leblond and Reebs, 2006). Studies have found that these more sociable individuals coordinate their movements more closely with conspecifics, which is a key element of coherent shoaling (Jolles et al, 2015(Jolles et al, , 2017Planas-Sitjà et al, 2018). Perhaps in line with this, Cote et al (2012) reported that western mosquitofish prefer to join shoals comprising sociable conspecifics over those made up of less sociable individuals.…”
Section: Behavioral Syndromesmentioning
confidence: 79%
“…Several studies have shown that cockroaches also display measurable behavioural variability in social cohesion [ 28 ], boldness [ 35 ], learning [ 36 ], behavioural plasticity [ 37 ] and thigmotaxis [ 38 ]. In the American cockroach ( Periplaneta americana ), individuals exhibit differences in the propensity to seek shelter, with some individuals settling faster and remaining longer within shelters than others [ 27 , 39 ]. These differences persist over time and contexts [ 37 ], indicating that this can be considered a personality trait.…”
Section: Introductionmentioning
confidence: 99%
“…These differences persist over time and contexts [ 37 ], indicating that this can be considered a personality trait. Faster sheltering individuals can play a key role in aggregation dynamics [ 40 ], leading to increased speed of aggregation and the number of aggregated individuals [ 39 ]. Whether these differences originate from differences in locomotory activity, sociality or photophobic response and whether they are genetically or socially induced is unknown.…”
Section: Introductionmentioning
confidence: 99%